Ethnography of Parno Marriage Customs in the Oral Tradition of Nagahi Koto Majidin Community, Kerinci, Jambi Province - Ravico; Muhammad Ridha DS; Samsul Bahry Harahap (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2024)
Abstract: This research aims to preserve the oral tradition or parno, which is currently experiencing a decline in interest among the younger generation of the Koto Majidin community, Kerinci. The study adopts an ethnographic model that encompasses 12 steps, involving interviews and participatory observation. Interviews were conducted with ‘ninik mamak’ (village elders), religious leaders, and community members involved in marriage traditions. Additionally, observations of wedding ceremonies were carried out to obtain comprehensive data. The research results show that the performance of ‘parno’ in marriage traditions consists of two main aspects: advisory performance and storytelling performance. ‘Parno’ in marriage traditions is a form of communication with a pattern of delivering advice rich in meaning, function, value, and norms. Based on these findings, a model for revitalizing the parno tradition is formulated into two programs: short-term and long-term. This model is developed based on the opinions and suggestions of informants as well as the researcher's observations. The short-term program includes activities that can be immediately implemented to attract the interest of the younger generation, while the long-term program focuses on sustainable efforts to maintain this tradition in the future. Abstrak: Penelitian ini bertujuan untuk melestarikan tradisi lisan atau parno yang saat ini mengalami pergeseran minat di kalangan generasi muda masyarakat Koto Majidin, Kerinci. Penelitian ini mengadopsi model etnografi yang mencakup 12 langkah, yang melibatkan wawancara dan observasi partisipatif. Wawancara terhadap ninik mamak, ulama, dan masyarakat yang terlibat dalam tradisi pernikahan. Selain itu, observasi terhadap upacara pernikahan juga dilakukan untuk memperoleh data yang komprehensif. Hasil penelitian menunjukkan bahwa performansi parno adat perkawinan terdiri dari dua aspek utama: performansi menasihati dan performansi bercerita. Parno adat perkawinan merupakan bentuk komunikasi yang memiliki pola penyampaian nasihat-nasihat yang kaya akan makna, fungsi, nilai, dan norma. Berdasarkan temuan tersebut, model revitalisasi tradisi parno dirumuskan dalam dua program, yaitu jangka panjang dan jangka pendek. Model ini disusun berdasarkan pendapat dan saran dari para informan serta hasil observasi peneliti. Program jangka pendek mencakup kegiatan-kegiatan yang dapat segera diimplementasikan untuk menarik minat generasi muda, sementara program jangka panjang difokuskan pada upaya berkelanjutan untuk mempertahankan tradisi ini di masa mendatang.